Outcomes reported in randomised clinical trials of major depressive disorder treatments in adolescents: a systematic scoping review protocol - Monsour, Andrea (BMJ Open, 2019)
INTRODUCTION: Major depressive disorder (MDD) is a common mental health condition in adolescents. Randomised clinical trials (RCTs) are the gold standard for assessing the safety and efficacy of interventions in this population. Heterogeneity in the outcomes measured and reported between RCTs limits the ability to compare, contrast, and combine trial results in a clinically meaningful way. There is currently no core outcome set (COS) available for use in RCTs evaluating interventions in adolescents with MDD. We will conduct a systematic scoping review of outcomes reported in adolescent depression RCTs to assess the variability of trial outcomes and to inform the development of a COS for adolescent MDD. METHODS AND ANALYSIS: We will apply methods based on the Joanna Briggs Institute scoping review methods manual. RCTs evaluating any treatment intervention for adolescent MDD published in the last 10 years will be located using an electronic bibliographic database search (MEDLINE, PsycINFO and Cochrane Central Register of Controlled Trials). Title and abstract screening, full-text screening, and data charting of eligible studies will be performed in duplicate. Outcomes identified will be mapped to an outcome-domain framework. Data analysis will include summary statistics of the characteristics of the included trials and outcomes. ETHICS AND DISSEMINATION: The results of this review will inform the development of a COS for adolescent MDD. The development and implementation of a COS for RCTs evaluating interventions in adolescents with MDD promise to help reduce variability in trial outcome selection, definition, measurement and reporting, ultimately facilitating evidence synthesis that will help to identify the best treatment practices for adolescents with MDD.